2022
DOI: 10.1128/aem.00594-22
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Anabaena sp. PCC 7938 as a Cyanobacterium Model for Biological ISRU on Mars

Abstract: The sustainability of crewed missions to Mars could be increased by biotechnologies which are connected to resources available on site via primary producers: diazotrophic, rock-leaching cyanobacteria. Indeed, this could greatly reduce the mass of payloads to be imported from Earth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The ability of cyanobacteria to grow in martian regolith also makes them ideal candidates for supporting human habitats on Mars. Recent research has indicated that cyanobacteria, functioning as an in-situ resource utilization (ISRU) system, could serve as the foundation for a biological life-support system by providing crucial nutrients for heterotrophic microbes 53 . Through this symbiotic relationship, they would not only sustain the growth of these heterotrophic microbes but also enable the production of plants as a vital source of food for humans on Mars.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cyanobacteria to grow in martian regolith also makes them ideal candidates for supporting human habitats on Mars. Recent research has indicated that cyanobacteria, functioning as an in-situ resource utilization (ISRU) system, could serve as the foundation for a biological life-support system by providing crucial nutrients for heterotrophic microbes 53 . Through this symbiotic relationship, they would not only sustain the growth of these heterotrophic microbes but also enable the production of plants as a vital source of food for humans on Mars.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospect for space applications could be to genetically engineer non-FR-adapted cyanobacterial strains in order to allow the synthesis of red-shifted chlorophylls and extend the available light spectrum (Luan et al, 2020;Liu et al, 2021). Potential background strains could be chosen for improvements in biomass production (Verseux et al, 2016;Liu et al, 2021;Ramalho et al, 2022), mineral resources extraction (Olsson-Francis and Cockell, 2010), or resistance to extreme conditions (Billi et al, 2022). Preliminary studies to partially incorporate FaRLiP components have already been performed in cyanobacteria (Shen et al, 2019;Trinugroho et al, 2020;Tros et al, 2020), albeit so far, a full integration of the complete gene set has yet to be achieved.…”
Section: Far-red Light Photosynthetic Adaptations In Cyanobacteriamentioning
confidence: 99%
“…They have evolved on Earth 3.5 mya (Sanchez-Baracaldo and Cardona, 2020;Hickman-Lewis et al, 2022) and are adapted to a wide range of environments, ranging from both hot and cold deserts (Friedmann, 1980;Wynn-Williams, 2000;Lacap-Bugler et al, 2017) with strong radiation (Rastogi et al, 2014) to high salinity habitats (Oren, 2015) and symbioses with lichens (Spribille et al, 2022) or plants (Rai et al, 2000). In addition, they have been proposed as suitable, multi-purpose microorganisms that are supportive during human missions to other planets including the selection of model strains (e.g., Ramalho et al, 2022). Researchers are able to not only isolate and grow them under artificial conditions, but also use them for large-scale industrial production of natural goods (Mutale-Joan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to this proposal, cyanobacteria would be fed with water mined from the ground; carbon and nitrogen sourced from the atmosphere 2 ; and the local regolith, from which it has been argued that they could extract the other necessary nutrients 3,4 . They would produce various consumables directly, such as dioxygen and dietary supplements, but also support the growth of secondary producers (e.g., plants 5 or microorganisms 2,6,7 ). These secondary producers could, in turn, generate a wide range of consumables including food, medicines, fuel precursors and structural materials 8,9 .…”
Section: Introductionmentioning
confidence: 99%